Faktor Risiko dengan Endometriosis pada Ibu Postpartum di RSUD Dr Moewardi Suarakarta - Putri Aprilliyanti; Faizah Betty Rahayuningsih (Jurnal Ners, 2025)
The continuous growth of endometrial tissue can cause pain, irritation, and infertility. Perimenstrual symptoms with or without abnormal bleeding, infertility, chronic fatigue. This disease occurs in 6–10% of women in their fertile period, but the exact incidence is unknown because this disease must be diagnosed through laparoscopy, so there can be a delay in diagnosis for years. This study aims to determine the risk factors for endometriosis in postpartum mothers at Dr. Moewardi Surakarta Regional General Hospital and analyze the relationship between risk factors and the incidence of endometriosis at Dr. Moewardi Surakarta Regional General Hospital. The type of research used is a quantitative study with a case-control design, which is an observational analytical study conducted by comparing the case group and the control group based on their exposure status. The sample in this study were postpartum mothers with endometriosis recorded in the medical records at Dr. Moewardi Surakarta Regional General Hospital. Moewardi Surakarta from January 2022 to June 2025 with a total of 200 postpartum mothers, including 100 postpartum mothers with endometriosis and 100 postpartum mothers without endometriosis. From the results of the bivariate analysis, a P value of 0.000 <0.05 was obtained, there was a relationship between age and endometriosis, a P value of 0.004 <0.05 was obtained, there was a relationship between preeclampsia and endometriosis, a P value of 0.000 <0.05 was obtained, there was a relationship between placenta previa and endometriosis, a P value of 0.154 > 0.05 was obtained, there was no relationship between parietas and endometriosis, a P value of 0.000 <0.05 was obtained, there was a relationship between dysmesnor and endometriosis, a P value of 0.001 <0.05 was obtained, there was a relationship between menstrual cycles and endometriosis. It is hoped that this research can be a reference for future researchers using different methods.